The Strategic Role of Digital Marketing in Moderating the Influence of Digital Literacy, Website Quality, and Ease of Access on the Brand Image - Dwi Utami Kusumastuti; Dini Handayani; Muhammad Fachrudin Arrozie (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The advancement of digital technology has transformed how people search for information and access health services. RSIA Clas C Cipondoh faces challenges related to its brand image, as indicated by low patient engagement with the hospital’s website and digital platforms, based on a preliminary survey. This study aims to analyze the simultaneous and partial effects of digital literacy, website quality, and ease of access on the brand image with digital marketing strategy as a moderating variable. A quantitative research method with a cross-sectional approach was employed. The study involved 152 outpatient respondents who had accessed the hospital website. Data were analyzed using index analysis with the Three Box Method and Moderated Regression Analysis (MRA) to test the moderating effect. Findings reveal that digital literacy, website quality, and ease of access simultaneously and significantly influence the hospital’s brand image. Partially, each of these variables also has a positive and significant effect on brand image. Moreover, the digital marketing strategy effectively moderates the relationships between digital literacy, website quality, and ease of access with brand image. The Three Box Method analysis indicates that although website quality falls into the high category, weaknesses remain in the interaction quality dimension. The study concludes that strengthening digital literacy, improving website quality, and ensuring ease of access supported by an effective digital marketing strategy can enhance the hospital’s brand image. Hospitals are advised to add interactive features such as chatboxes or live chat to improve patient engagement and online service experience.